Analysis of Predisposing Factors Related to Compliance With the Use of Personal Protective Equipment in the Textile Industry - Nur 'Aini Azhari Nugrahani; Dwi Astuti (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Indonesia is a developing country in all industrial sectors, including the textile industry. The Sari Warna Asli Tekstil II Company is a textile industry that produces everything from cotton to ready-made clothing. The Sari Warna Asli Tekstil II Company experienced work accidents caused by several reasons, including a lack of discipline and a need to understand the importance of using complete personal protective equipment. This study aimed to determine predisposing factors related to compliance with the use of personal protective equipment. This research uses an analytical observational method with a cross-sectional approach. This research was conducted at the Sari Warna Asli Company II, which is located at street Randusari, Teras, Dusun I, Randusari, Boyolali, Boyolali Regency, Central Java. This research will be conducted from September to October 2023. The population in this research is all employees in the spinning section of the Sari Warna Asli Tekstil II Company, totalling 914 people. The sampling technique used was the incidental sampling technique, obtaining a sample of 100 people. Primary data collection uses a questionnaire. Data analysis for this study used bivariate analysis with the chi-square test. Data was analyzed using the Statistical Product and Service Solution (SPSS) version 20 software. The research results showed that there was a relationship between knowledge and compliance with the use of personal protective equipment (p-value = 0.000), there was a relationship between working period and compliance with the use of personal protective equipment (p-value = 0.000), and there is no relationship between education and compliance with the use of personal protective equipment (p-value = 0.567). It is recommended that companies should increase regulations related to occupational safety and health programs because some employees still do not comply with using personal protective equipment and continue to make efforts to increase employee knowledge.Keywords: Compliance, Education, Knowledge, Personal protective equipment, Working period